PERKEMBANGAN BISNIS HOTEL SYARIAH DI INDONESIA (Studi Kasus Pengembangan Hotel Syariah di Lombok Provinsi Nusa Tenggara Barat) - A. Zamakhsyari Baharuddin; Fahadil Amin Al Hasan (Al-'Adl, 2018)
Halal tourism is one of the sectors in Islamic Economy which has a significant development. In this case Sharia Hotel is an inseparable part of the halal tourism sector. West Nusa Tenggara as one of the provinces set by the government as a halal tourism destination in Indonesia should be an example in the implementation of strategic development of halal tourism in Indonesia. If the province is successful in implementing the strategy, then the success will be followed by other provinces. In terms of the development of sharia hotels, West Nusa Tenggara can be said to be more advanced than other provinces. The number of hotels that are certified halal MUI is quite a lot, although the number of certified hotels is still less when compared with hotels that are not halal certified. One of the obstacles is that there are still entrepreneurs who misunderstand the concept of halal halal tourism. This paper provides a general overview of the development of sharia business in Indonesia, especially for the West Nusa Tenggara region as one of the halal tourism destinations set by the Ministry of Tourism Republic of Indonesia.